Effectiveness and safety of a hydrophobic aspheric monofocal intraocular lens with molding process for cataract surgery - Liang-ping Liu; Ying-yan Qin; Qiang Lu; Qiang Wu; Guang-ying Zheng; Yi-yong Qian; Ying-zi Pan; Zhe-ming Wu; Jie-wei Liu; Hong-pei Ji; Xu-dong Huang; Ming-xing Wu (BMC Ophthalmology)
Abstract Background To evaluate the effectiveness and safety of a novel hydrophobic aspheric monofocal intraocular lens (IOL) in cataract surgery. Methods This is a prospective, multicenter, randomized, open-label, parallel-controlled clinical study, conducted at nine sites in P.R. China. Eligible participants were adults aged 60–80 years with a diagnosis of age-related cataract scheduled for phacoemulsification combined with IOL implantation. Subjects were randomly assigned to receive either the aspheric monofocal IOL (SM60AS, Henan Simedice Biotechnology Co. Ltd., Zhengzhou, China) or the control IOL (SN60WF Alcon Laboratories Inc.). Postoperative outcomes including uncorrected distance visual acuity (UDVA), best-corrected distance visual acuity (CDVA), refractive status, and complications were assessed and compared between the two groups at each follow-up visit. Results A total of 173 patients completed the study, including 88 in the SM60AS group and 85 in the SN60WF group. No statistically significant differences were found in CDVA between the two groups at any postoperative visit. Although the SM60AS group showed slightly lower UDVA at day 1, day 7 (p < 0.01) and 12 months (p < 0.05), there were no statistically significant differences in UDVA between the groups at 1, 3, and 6 months. The SM60AS group exhibited a slightly more myopic refractive outcome compared to the control group, while residual astigmatism remained comparable. No serious IOL-related complications were reported in either group. Conclusion The novel SM60AS IOL demonstrated satisfactory effectiveness and safety, with clinical outcomes comparable to those of the established control IOL in cataract surgery. Trial registration The trial was officially registered on August 29, 2020, in the Chinese Clinical Trial Registry, with the registration number: ChiCTR2000037527 ( https://www.chictr.org.cn/showproj.html?proj=60164 ).